2011
DOI: 10.1080/03630242.2011.540744
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HPV Knowledge in the Era of HPV Vaccination: A Study of Unvaccinated Young Adult Women

Abstract: Until recently, awareness of the sexually transmitted infection human papillomavirus-the virus that causes cervical cancerwas relatively low. The purpose of this study was to identify factors associated with human papillomavirus knowledge now that human papillomavirus vaccines have become widely available. Young adult women (n D 739; aged 18-26 years) attending Florida State University who had not yet initiated human papillomavirus vaccination completed a survey between March-August 2009. The survey assessed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 28 publications
9
45
2
1
Order By: Relevance
“…Consistent with previous studies that were conducted among young women at various universities (Dillard & Spear, 2010;Gerend & Shepherd, 2011;Head et al, 2009;Lopez & McMahan, 2007), over 90% of college women in both groups knew that that routine Pap test needs to be continued after the vaccination. They also knew that HPV vaccine does not protect against other STIs.…”
Section: Indirect Predictors Of Hpv Vaccine Uptakesupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with previous studies that were conducted among young women at various universities (Dillard & Spear, 2010;Gerend & Shepherd, 2011;Head et al, 2009;Lopez & McMahan, 2007), over 90% of college women in both groups knew that that routine Pap test needs to be continued after the vaccination. They also knew that HPV vaccine does not protect against other STIs.…”
Section: Indirect Predictors Of Hpv Vaccine Uptakesupporting
confidence: 74%
“…Many of them (79.2%) also could not identify ways to prevent themselves from acquiring cervical cancer. A more recent study was conducted in 2009 among 739 college women (Gerend & Shepherd, 2011). The study reported that over 97% of college women who have not received the vaccine were aware of HPV.…”
Section: Hpv Vaccine Controversymentioning
confidence: 99%
“…Many of the previous studies assessing patient knowledge of HPV surveyed only women and examined HPV knowledge relating to cervical cancer and HPV vaccination. [11] In this study, healthcare providers had spoken to women about HPV significantly more than men. However, healthcare providers had not spoken to either group very often, with women being at the midpoint of the scale (1.5) and men being far below the midpoint (0.6).…”
Section: Discussionmentioning
confidence: 99%
“…[10] In a recent study examining general knowledge of HPV in the post-vaccine era, 97% of college females had heard of HPV and 84% knew that there was a link between HPV and cervical cancer. [11] Very few studies included men's perceptions and understanding of HPV as it relates to cervical cancer. The effectiveness of the HPV vaccine against oral HPV infection is unknown and vaccination is not currently recommended for the primary prevention of oropharyngeal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest a limited awareness and knowledge of HPV (Brabin et al, 2006;Friedman & Shepeard, 2007), including among unvaccinated young women (Gerend & Shepherd, 2011). Yet, HPV awareness may be increasing, largely due to the approval of the vaccine and the subsequent media campaign (Bendeik, Mayo, & Parker, 2011;Christian, Christian, & Hopenhayn, 2009;Hopenhayn et al, 2007).…”
Section: Introductionmentioning
confidence: 97%